Use of integrated geriatric assessment for social problems in the elderly - Montenegro Saldaña, Luis (2009)
Introduction: With recent avances in medical care available there is an increasing number of persons included in the so called advanced age group or elderly. For this reason, the health of the elderly is now a very important topic to be studied from a social point of view. Objective: To determine social problems prevalent in the elderly. Material and Methods: A descriptive cross-sectional study was performed by interviewing 154 persons more than 60 years old who came to a health and metabolic control campaign organized by the Geriatrics Service in September 2005 in Guillarmo Almenara-Irigoyen National Hospital. Results: The average age of participants was 72.1 ± 8 years (range: 60 to 91 years), and 59.7 (92) were female. Diagnosis criteria for ease of falling syndrome were found in 48.1% of participants, urinary incontinence of any cause in 40.3%, dismotility in 6.5%, and mild to major cognitive impairment in 63.6%. Seventy-four (48.1%) persons had at least one major criterion for defining frailty and were classified as being frail. Using the Gijon test modified by Cayetano Heredia University, we found that 49.4% of interviewed persons had social risks and/or problems, and 12 persons (7.8%) were identified as having social problems. Nearly one of nine (11.5%) of interviewees live with a similarly aged spouse, and 8.7% live on their own, or their children have moved away form the parental home. Half of the participants (50.7%) receive a minimal monthly allowance (from retirement public funds) or do not receive any income, 9.1% have their house in poor conditions (humid environment, incomplete building, or inadequately built). With respect to social networks, 29.9% have established relationthips only with their relatives, and do not get out of their home, while 28.6% require in-house care or permanent care. Conclusions: This integrated geriatric assessment is an important parto of any complete study performed in elderly people at any healthcare level.